2015
DOI: 10.2334/josnusd.57.67
|View full text |Cite
|
Sign up to set email alerts
|

Effects of initial periodontal therapy on interleukin-1β level in gingival crevicular fluid and clinical periodontal parameters

Abstract: Inflammatory cytokines may have important roles in periodontitis.We assessed the effects of initial periodontal therapy on clinical periodontal parameters and interleukin-1β (IL-1β) level in gingival crevicular fluid (GCF) from chronic periodontitis (CP) patients. After initial screening, baseline periodontal parameters such as probing pocket depth (PPD) and bleeding on probing (BOP) were measured. GCF samples were collected from 13 shallow (≤3 mm) and deep (≥5 mm) PPD sites from 13 CP patients, and GCF volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 19 publications
(28 reference statements)
5
31
0
Order By: Relevance
“…Moreover, we observed that HES significantly downregulated the mRNA expression levels of IL‐1β, IL‐6, and iNOS in the L+H groups compared with those in the Lig group (Figure ). The destructive roles of proinflammatory cytokines during periodontal infection have been previously discussed, and IL‐1β and IL‐6 are signature innate cytokines that have been characteristically associated with inflammatory cell migration and osteoclastogenesis . The attenuated mRNA expression levels of IL‐1β, IL‐6, and iNOS under HES treatment observed in this study are consistent with the findings of in vivo studies on the anti‐inflammatory activity of HES in the models of cerebral ischemia 21 and lipopolysaccharide (LPS)‐induced acute lung inflammation .…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, we observed that HES significantly downregulated the mRNA expression levels of IL‐1β, IL‐6, and iNOS in the L+H groups compared with those in the Lig group (Figure ). The destructive roles of proinflammatory cytokines during periodontal infection have been previously discussed, and IL‐1β and IL‐6 are signature innate cytokines that have been characteristically associated with inflammatory cell migration and osteoclastogenesis . The attenuated mRNA expression levels of IL‐1β, IL‐6, and iNOS under HES treatment observed in this study are consistent with the findings of in vivo studies on the anti‐inflammatory activity of HES in the models of cerebral ischemia 21 and lipopolysaccharide (LPS)‐induced acute lung inflammation .…”
Section: Discussionsupporting
confidence: 88%
“…In an effort to better understand the reasons for this, and eventually find a biomarker that could predict disease activity at the level of the site, the concentrations of selected cytokines have been assessed at multiple sites in some patients. In periodontitis patients, il‐1β was found to be higher in deep active lesions compared to healthy gingiva (Fujita, Ito, Sekino, & Numabe, ; Gamonal, Acevedo, Bascones, Jorge, & Silva, ; Oh, Hirano, Takai, & Ogata, ; Reis, Da Costa, Guimaraes, et al, ; Thunell, Tymkiw, Johnson, et al, ; Toker, Poyraz, & Eren, ). The same was reported for interferon (ifn)‐γ, il‐6, il‐8, and tnf‐α (Dutzan, Vernal, Hernandez, et al, ; Fujita et al, ; Papathanasiou, Teles, Griffin, et al, ; Reis et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…IL‐1β is an important mediator of inflammatory response involved in the pathophysiology of gingivitis and periodontitis. Two studies have reported correlations between the inflammatory status of periodontal disease and IL‐1β levels in gingival tissues and gingival crevicular fluid (GCF) 5 , 6 . Expression of IL‐1β induces expression of adhesion molecules and production of chemokines, such as IL‐8, by epithelial cells, resulting in recruitment of inflammatory cells to the site 7 , 8 .…”
mentioning
confidence: 99%